1993
DOI: 10.1111/j.1365-2184.1993.tb00005.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of replicative senescence by 5‐azacytidine: fundamental cell kinetic differences between human diploid fibroblasts and NIH‐3T3 cells

Abstract: To analyse the putative role of methylation of cytosine residues in the nuclear DNA as a regulatory step during cellular ageing, we incubated ageing human amniotic fluid derived fibroblast-like cells and non-ageing NIH-3T3 cells with 5-azacytidine. BrdUrd/Hoechst and acridine orange (AO) flow cytometry was used to compare the effects of the base analogue on cell proliferation and cell differentiation. In NIH-3T3 cultures, 96h exposures to 4 microM 5-azacytidine caused diminished cell proliferation due to cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…A loss of 5mC residues from the genome of human fibroblasts is also observed with increasing passage number (433). More importantly, several investigators (88,144,427) have shown that incubating human fibroblasts with 5-azacytidine, a compound that inhibits the methylation of cytosine in DNA and results in the hypomethylation of DNA, shortens the in vitro life span of human fibroblasts; that is, the number of population doublings was reduced after 5-azacytidine treatment.…”
Section: Factors That Regulate Transcriptionmentioning
confidence: 99%
“…A loss of 5mC residues from the genome of human fibroblasts is also observed with increasing passage number (433). More importantly, several investigators (88,144,427) have shown that incubating human fibroblasts with 5-azacytidine, a compound that inhibits the methylation of cytosine in DNA and results in the hypomethylation of DNA, shortens the in vitro life span of human fibroblasts; that is, the number of population doublings was reduced after 5-azacytidine treatment.…”
Section: Factors That Regulate Transcriptionmentioning
confidence: 99%
“…Simultaneous staining of DNA with a BrdUrd-nonsensitive fluorochrome such as PI or ethidium bromide (EB) allows analysis of cells in G1-, S-, and G2/M-phases of several cell cycles. The continuous BrdUrd labeling technique, apply-ing the BrdUrd/Hoechst quenching effect, has been used for cell kinetic analysis of initially synchronous cell populations (4)(5)(6)(7)(8)(9)(10)(11)(12) and asynchronously dividing cells (13)(14)(15), resolving the complete history of cell proliferation and representing the heterogeneity of the proliferative status of cell populations. The BrdUrd/Hoechst quenching effect has also been applied for detecting DNA-replicating cells after pulse labeling with BrdUrd by staining cells with HO 33342 and mitramycin (MI), a dye whose fluorescence is enhanced by the incorporation of BrdUrd into DNA (16,17).…”
mentioning
confidence: 99%
“…DNA damage (57), oxidative stress (14), histone deacetylase inhibitors (48), methylation inhibitors (71), and expression of some activated oncogenes, such as Ras, Raf, or MEK (59,75). Some conditions, such as prolonged culture under hyperoxic conditions, can accelerate the rate of telomere attrition (73), but most of the "premature senescence" states occur rapidly and appear to be independent of telomere length (45,69).…”
mentioning
confidence: 99%